A cross sectional observational study to evaluate the maternal and fetal outcome in postdated pregnancies - Narayan, Ritika; R., Sheela S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Post-dated pregnancy is when the gestation is more than 40 weeks or 280 days. They last longer than the estimated date of delivery. Postdated pregnancies are associated with increased perinatal and maternal complications. These risks are greater than it was originally thought. Risks have been underestimated in the past leading to increasing number of complicated postdated pregnancies which appears to be otherwise low risk. The maternal risks are very often underappreciated resulting in increased maternal morbidity. Methods: This cross sectional observational study was done to evaluate maternal and fetal complications associated with Postdated pregnancies was carried out in the department of obstetrics and gynecology in a tertiary care centre, Sir Devraj Urs Medical College and RL Jalappa Hospital, Kolar between July 2018 and July 2019, fulfilling all the inclusion and exclusion criteria. Results: 50 out of 100 patients had full term normal deliveries where as 45% patients required cesarean section. Most common indication for cesarean section was meconium stained liquor with fetal distress (25%). 42% of the babies born needed NICU admission. Most common maternal complication seen was Postpartum Hemorrhage. Conclusions: The present study we conclude that postdated pregnancy was associated with significant risk of perinatal complications such as fetal distress, meconium aspiration syndrome and IUGR. There was increased risk of obstetric complications as well like atonic PPH, oligohydramnios, obstructed labor.